2013
DOI: 10.1111/jam.12390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus acidophilus and inulin on faecal viral shedding and immunization against H9 N2 Avian influenza virus

Abstract: Aims: The aims of this investigation were to compare the effects of Lactobacillus acidophilus addition as simple or microencapsulated (ME) probiotic and inulin as prebiotic to the broiler diet on the faecal viral shedding and immunization against avian influenza virus (AIV) with or without H 9 N 2 vaccination. Methods and Results: Simple or ME forms of Lact. acidophilus, inulin and combination of them as synbiotic were analysed for their ability to enhance immunity against H 9 N 2 AIV and to decrease faecal vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Regarding other animal models, Poorbaghi et al showed that microencapsulated Lactobacillus acidophilus probiotic and its symbiotic form with inulin decreased faecal shedding of H9N2 avian influenza virus (AIV) in both non-vaccinated and vaccinated broiler chicks [ 62 ]. In another study, Enterococcus faecalis-1 has been proved to improve the body weight and feed conversion ratio of treated broilers, and also significantly elevated the total IgY serum level, resulting in efficient modulation of the cecal microbiota and decrease in the mortality percentage of broilers [ 63 ].…”
Section: Immunomodulatory Role Of Probiotics On Influenza Virus In Thmentioning
confidence: 99%
“…Regarding other animal models, Poorbaghi et al showed that microencapsulated Lactobacillus acidophilus probiotic and its symbiotic form with inulin decreased faecal shedding of H9N2 avian influenza virus (AIV) in both non-vaccinated and vaccinated broiler chicks [ 62 ]. In another study, Enterococcus faecalis-1 has been proved to improve the body weight and feed conversion ratio of treated broilers, and also significantly elevated the total IgY serum level, resulting in efficient modulation of the cecal microbiota and decrease in the mortality percentage of broilers [ 63 ].…”
Section: Immunomodulatory Role Of Probiotics On Influenza Virus In Thmentioning
confidence: 99%
“…Also, the effects of ME form of probiotic are more remarkable in the reduction of viral fecal shedding detected by RT-PCR (Poorbaghi et al, 2014). In this study, simple or ME forms of L. acidophilus, inulin, and a combination of them as synbiotic were analyzed for their ability to enhance immunity against H 9 N 2 AIV and to decrease fecal viral shedding in Cobb-500 broiler chicks.…”
Section: Immunity Against Aivsmentioning
confidence: 99%
“…These bacteria are considered as generally recognized as safe (GRAS) microorganisms and can be safely used for medical and veterinary applications (Fuller, 1989). Lactobacilli are important organisms recognized for their fermentative ability as well as their health and nutritional benefits (Poorbaghi et al, 2014). They produce various compounds such as organic acids, diacetyl, hydrogen peroxide, bacteriocin and other bactericidal proteins during lactic fermentations (Ravi et al, 2011).…”
mentioning
confidence: 99%